Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3133/ofr20111313
|View full text |Cite
|
Sign up to set email alerts
|

Mountain goat abundance and population trends in the Olympic Mountains, Washington, 2011

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Therefore, direct anthropogenic impacts are assumed to be minimal. Grazing pressure and disturbance from introduced mountain goats ( Oreamnos americanus Blainville, 1816) pose an increasing impact to high elevation plant communities in the Olympic Mountains ( Houston et al 1994 , Jenkins et al 2012 ), and goats were observed in the vicinity of populations of S. basaltica on Mt. Angeles during the visit in 2016; however, no evidence of direct grazing or damage to S. basaltica was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, direct anthropogenic impacts are assumed to be minimal. Grazing pressure and disturbance from introduced mountain goats ( Oreamnos americanus Blainville, 1816) pose an increasing impact to high elevation plant communities in the Olympic Mountains ( Houston et al 1994 , Jenkins et al 2012 ), and goats were observed in the vicinity of populations of S. basaltica on Mt. Angeles during the visit in 2016; however, no evidence of direct grazing or damage to S. basaltica was detected.…”
Section: Resultsmentioning
confidence: 99%